Climate-induced shifts in composition and protection regulate temperature sensitivity of carbon decomposition through soil profile. (September 2022) - Mao, Xiali; Zheng, Jinyang; Yu, Wu; Guo, Xiaowei; Xu, Kang; Zhao, Ruiying; Xiao, Liujun; Wang, Mingming; Jiang, Yefeng; Zhang, Shuai; Luo, Lun; Chang, Jinfeng; et al.
Abstract: Through soil profile, both chemical composition of soil organic carbon (SOC) and edaphic physiochemical properties present a vertical gradient, likely resulting in depth-specific SOC dynamics in response to climate change (e.g., global warming). We assessed temperature sensitivity of SOC decomposition ( Q 10 ) by incubating (128 days) soils sampled across five sequential layer depths (i.e., 0–10, 10–20, 20–30, 30–50, and 50–100 cm) at ten sites along a ∼2500 m elevational transect (from ∼2100 m to ∼4600 m) covering various vegetation types (from evergreen broadleaved forest to alpine meadow) in southeast Tibet, China. The Q 10 of SOC decomposition was significantly affected by both soil depth and elevation. However, depth-induced variation of Q 10 was much smaller than that induced by the elevation gradient. Across the ten sites and five soil depths, chemical composition of SOC and its physiochemical protection against decomposition contributed >80% to the explained variance of Q 10 values. Path analysis suggested that climate indirectly affected Q 10 via its regulation on chemical composition of SOC and their physiochemical stabilization. The results from a carbon model constrained by the collected data further revealed that fast, slow and passive SOC pools exhibited significant difference in their Q 10, resulted from different involvement of chemical composition and physicochemical protection in their decomposition. Our findings demonstrate similar temperature sensitivity of SOC decomposition across soil depths, but spatially heterogeneous temperature sensitivity due to climate-induced variability of both chemical recalcitrance of SOC and its physiochemical protection against decomposition. Highlights: Q10 down to 1 m along a 2500 m elevational transect was investigated. Q10 are constant across soil depths, but different among vegetation types. Molecular composition and physical protection are predominant controls over Q10 . Climate indirectly affects Q10 by its effect on SOC composition and stabilization.